PENGARUH KARAKTERISTIK AUDITOR INTERNAL, KOMITMEN ORGANISASI, GAYA KEPEMIMPINAN TERHADAP KUALITAS HASIL PEMERIKSAAN - Eva Solina (Sekolah Tinggi Ilmu Ekonomi AMM, 2016)
The purpose of this study is to analyze the effect of characteristic from internal auditor (independency, objectivity, and competence) organizational commitments, and leadership style influence quality of audit result by APIP in the inspectorate office at the island of Lombok. Data were collected through a distribution of questionnaire to 102 internal auditor (JFA and P2UPD) as the sample from 125 total population. Hypothesis testing based on linear regression show that the objectivity, competence, and organizational commitments, has positive and significant influence to quality of audit result. While independency and leadership style partially doesn’t influence to quality of audit result